Hospitality and social reintegration of convicted individuals - dos Santos Araújo, Larissa (2024)
This study addresses hospitality and the social reintegration of inmates.  According to the APAC method, the objective is to investigate how hospitality manifests in the treatment of inmates at the Social Reintegration Center (SRC) in São Luís-Maranhão. Methodologically, this study is exploratory and descriptive, employing a qualitative approach. We collected data through semi-structured interviews with three SRC employees, considered here as “hosts”, and eight inmates. After transcription, the Content Analysis technique was applied to the interviews. The results indicate that SRC inmates and staff perceive hospitality in both tangible and intangible aspects. These elements were organized into the following dimensions: treatment with the residents; treatment with the family members; infrastructure and comfort; food; interaction; and services. 19 topics related to hospitality were identified. The employees perceived almost all these aspects, while the inmates emphasized elements related primarily to their treatment, the treatment of their families, and the food provided. The findings suggest the positive contribution of hospitality to the social reintegration process of incarcerated individuals.